STUDI EFISIENSI VOLUME MATERIAL DAN ESTIMASI BIAYA BANGUNAN MENGGUNAKAN BIM 5D DENGAN SOFTWARE TEKLA STRUCTURES (Studi Kasus Pembangunan Gedung Perpustakaan Desa Gunung Rajak) - Hafiz Hamdani; Ahmad Zarkasi; M Ramdani Novaldi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Efforts to improve the efficiency of planning and cost control in small- to mediumscale construction projects in rural areas, the digital approach through Building Information Modeling (BIM) 5D offers a promising alternative. This study aims toanalyze the efficiency of material volume and cost estimation using the BIM 5D-based software Tekla Structures, with a case study on the construction project of the Gunung Rajak Village Library Building, Sakra Barat District, East Lombok Regency. The secondary data used include Shop Drawings and the Bill of Quantities (BoQ) btainedfrom the implementing contractor. The structural modeling was carried out using Tekla Structures to automatically generate estimates of concrete volume and reinforcement weight, which were then compared with conventional methods tomeasure differences and efficiency. The analyzed structural elements include foundations, tie beams, columns, beams, floor slabs, and the roof. The results show that the use of BIM 5D produces more accurate volume and cost estimations andaccelerates the calculation process. The  ifferences in concrete volume reached 18.14%, reinforcement weight 3.05%, and roof volume 9.53%, while cost efficiency was around 14.8% compared to the conventional method. These findings indicate that the implementation of BIM 5D has the potential to improve material and budget efficiency, although its application in rural areas still faces technical and human resource constraints.